Adoption and Actual Usage of SaaS-Based Cloud Applications Among the Swedish SMEs—A TAM-TOE Integrated Perspective - Muhammad Shehzad Hanif; Aitzaz Khurshid; Dariia Kulibaba; Ammaz Sajid (Human Behavior and Emerging Technologies)
The cloud-based software-as-a-service (SaaS) model delivers corporate software to organizations as a service over the internet, minimizing investment in on-premises facilities and automatically adapting IT resources to meet demand variations. Integrating the two popular technology adoption frameworks, the technology acceptance model (TAM) and the technology, organization, and environment (TOE) framework, this study employs a structural equation modeling technique on a carefully chosen sample of 204 technology-intensive small and medium-sized enterprises (SMEs) in Sweden to investigate the effect of various antecedents on the intention and actual utilization of SaaS-based cloud applications. The results are counterintuitive regarding the relationship between perceived ease of use and intention and the inverse relationship between risk and trust. The central construct of TAM has an insignificant relationship with the intention to adopt SaaS applications, leading to substantial practical implications for Swedish SMEs. Similarly, a significant effect of trust with an insignificant impact of risk on intention challenges conventional wisdom. The novel integration of the two models also makes substantial theoretical contributions.